Profil Karakteristik, Pengetahuan dan Sikap Remaja terhadap Konseling Tiga Ancaman Dasar Kesehatan Reproduksi Remaja : Profile of Characteristics, Knowledge and Attitudes of Adolescents towards Counseling Three Basic Threats to Adolescent Reproductive Health - Yulianti, Nova; Suri Nurharjanti; Gita Nur Fitrianingsih; Dwi Ratna Prima; Tiarlin Lavida R (Indonesian Journal of Midwifery (IJM), 2024)
Based on SDKI data in 2017, the results show that sexual behavior in male adolescents is 59% and 74% of women have had sexual intercourse before marriage at the age of 15-19 years. According to Kominfo Data 2021 Explains that Drug Use Among Teenagers Aged 15-35 Years With a Percentage of 82.4% Status as Users. Data from the IDAI (Indonesian Pediatric Association) Report There are 741 Hiv Teenagers in the 15-19 Year Age Group. To overcome the problem of adolescents, among them is through the formation of PIK Remaja / Student. This research method is quantitative research using the Pre Experimental Design Research Method with One Group Pre Test-Post Test Design. The number of samples in this study amounted to 46 respondents aged 17-19 years. The results showed that the characteristics of respondents were mostly 17 years old (65.2%), the gender of respondents was male (60.9%), parents' education (60.9%) with the last education graduated from high school, parents' work (50.0%) with private employee jobs, positive peer influence as many as 33 people (71.7%), sources of information from health workers (doctors, midwives, nurses) (39.1%), got negative family support which was 29 people (63%). The value of knowledge before being given counseling intervention most of the students were less which amounted to 46 people (100%) and after being given counseling intervention most of the students had good knowledge which amounted to 26 people (56.5%). The attitude value before being given counseling intervention, most students had a positive attitude which amounted to 29 people (63%) and after being given counseling intervention, most students had a positive attitude which amounted to 37 people (80.4%).   Abstrak Berdasarkan Data SDKI Pada Tahun 2017 Mendapatkan Hasil Bahwa Perilaku Seks Pada Remaja Pria Sebanyak 59% Dan 74%  Pada Wanita Sudah Melakukan Hubungan Seksual Sebelum Menikah Pada Usia 15–19 Tahun. Menurut Data Kominfo 2021 Menerangkan Bahwa Penggunaan Narkoba Pada Kalangan Remaja Berusia 15-35 Tahun Dengan Persentase 82,4% Berstatus Sebagai Pemakai. Data Laporan IDAI (Ikatan Dokter Anak Indonesia) Terdapat 741 Remaja Hiv Pada Kelompok Usia 15-19 Tahun. Untuk Mengatasi Masalah Remaja Tersebut Diantaranya Melalui Pembentukan PIK Remaja/Mahasiswa. Metode Penelitian Ini Adalah Penelitian Kuantitatif Menggunakan Metode Penelitian Pre Experimental Design Dengan Desain One Group Pre Test-Post Test Design. Jumlah Sampel Pada Penelitian Ini Berjumlah 46 Responden Yang Berusia 17-19 Tahun. Hasil penelitian menyebutkan bahwa karakteristik responden sebagian besar yang memiliki umur 17 tahun (65,2%), jenis kelamin responden adalah laki-laki (60.9%), pendidikan orang tua (60.9%) dengan pendidikan terakhir tamat SMA, pekerjaan orang tua (50.0%) dengan pekerjaan karyawan swasta, pengaruh teman sebaya positif sebanyak 33 orang (71,7%), sumber infomasi dari Tenaga kesehatan ( dokter, bidan, perawat) (39.1%), mendapat dukungan keluarga yang negatif  yaitu 29 orang (63%). Nilai pengetahuan sebelum diberikan intervensi konseling sebagian besar siswa-siswi kurang yang berjumlah 46 orang (100%) dan sesudah diberikan intervensi konseling siswa-siswi sebagian besar memiliki pengetahuan baik yang berjumlah 26  orang (56.5%). Nilai sikap sebelum diberikan intervensi konseling sebagian besar siswa-siswi memiliki sikap positif yang berjumlah 29 orang (63%) dan sesudah diberikan intervensi konseling siswa-siswi sebagian besar memiliki sikap positif yang berjumlah 37 orang (80.4%).